A cost effectiveness analysis of stepped care treatment for bulimia nervosa. - Crow, S; Agras, W; Halmi, K; Fairburn, C; Mitchell, J; Nyman, J (2013)
BACKGROUND: The cost effectiveness of various treatment strategies for bulimia nervosa (BN) is unknown. AIMS: To examine the cost effectiveness of stepped care treatment for BN. METHOD: Randomized trial conducted at four clinical centers with intensive measurement of direct medical costs and repeated measurement of subject quality of life and family/significant other time involvement. Two hundred ninety-three women who met DSM-IV criteria for BN received stepped care treatment or cognitive behavioral therapy. Cost effectiveness ratios were compared. RESULTS: The cost per abstinent subject was $12,146 for stepped care, and $20,317 for cognitive behavioral therapy. Quality of life ratings improved significantly with treatment, and family/significant other time burden diminished substantially. DISCUSSION: In this trial, stepped care for BN appeared cost effective in comparison to cognitive behavioral therapy. Treatment was associated with improved quality of life and diminished time costs of illness.